2001
DOI: 10.1136/jech.55.10.731
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' proxy reports of parents' socioeconomic status: How valid are they?

Abstract: Study objective-Children's proxy reports on indicators of their parents' socioeconomic status (SES) have either been used uncritically or dismissed as invalid. This paper examines the validity of young adolescents' reports of parental SES by comparing adolescent reports with parents' own reports of SES. Design, setting and participants-In 1990, 924 13 year olds, along with 648 of their fathers and 735 of their mothers, participated in the baseline survey of The Norwegian Longitudinal Health Behaviour Study. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
187
5
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(206 citation statements)
references
References 17 publications
8
187
5
6
Order By: Relevance
“…35 The occupational measure was based on the adolescents' reports, but although the proportion of missing could be substantial on this type of question, the adolescents are usually able to provide valid answers. 14,15 There were, however, some difficulties in assigning the occupations into different social groups, especially the upper managerial group. Social desirability in reporting could bias the association between BMI and SES as both were self-reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The occupational measure was based on the adolescents' reports, but although the proportion of missing could be substantial on this type of question, the adolescents are usually able to provide valid answers. 14,15 There were, however, some difficulties in assigning the occupations into different social groups, especially the upper managerial group. Social desirability in reporting could bias the association between BMI and SES as both were self-reported.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the SES of adolescents is much discussed owing to the difficulty of obtaining valid data on parental SES, [12][13][14][15] and because adolescents have not obtained their own SES. Friestad et al 16 studied the stability of educational plans in a longitudinal study, and found that planning for academic studies showed high stability between ages 13 and 15, and did track into studying rather than working at age 18.…”
Section: Introductionmentioning
confidence: 99%
“…Students with missing data (compared with the reference group) were not significantly different in likelihood of reporting daily dietary intake outcomes and inclusion of the variable for missing data did not substantially change the significance or point estimates of other coefficients. Further, previous studies have shown acceptable consistency between child-and parent-reported measures of father's and mother's education (52) and alternative student reports of SES, such as household affluence (53,54) . Although we acknowledge the limitations inherent in using studentreported parent education, the selection of this variable as a primary explanatory variable was based on our review of the literature and evidence that parent education is the most frequently used measure in nutrition research to evaluate child and adolescent SES (6,(27)(28)(29)(30)(31)44,55) , particularly in adolescent nutrition studies (27)(28)(29)(30)(31) .…”
Section: Discussionmentioning
confidence: 99%
“…The validity of the information on parental occupation given by the adolescents has been investigated in several studies, most often by comparing these data with information supplied by the parents and calculating percentage-agreement and Kappa coefficients [210][211][212][213][214][215][216][217]. All of the studies conclude that adolescents were able to give reliable information concerning their parent's occupation.…”
Section: Discussionmentioning
confidence: 99%